Analysis of Successful Implementation of Hospital Information System in Bhayangkara Polda DIY Hospital with MMUST Method - Afriliya Hayati; Savitri Citra Budi (Media Kesehatan Masyarakat Indonesia, 2025)
Since 2010, Bhayangkara Polda DIY Hospital has been using Hospital Information System (HIS), but the system still needs to be optimized. In the context of optimizing HIS implementation, it is necessary to analyze the success of HIS implementation. This study examines the factors that influence the successful implementation of Hospital Information System (HIS) in Bhayangkara Polda DIY Hospital based on the Model for Mandatory Use of Software Technologies (MMUST) method. This research is a descriptive study with a cross-sectional quantitative approach. The study sample used purposive sampling, which amounted to 98 respondents. Data analysis using the Structural Equation Modeling Partial Least Squares (SEM-PLS) technique using SmartPLS software version 4.1.0.3. The results stated that information satisfaction is influenced by information quality, performance expectations are influenced by information satisfaction and social influence, performance expectations and facility conditions influence attitudes, attitudes influence usage and overall satisfaction, and net benefits are influenced by usage and overall satisfaction. This study proves empirically that all hypotheses are accepted. HIS has proven to be a successful implementation because it can produce accurate, fast, and complete information, accelerate user performance, and provide benefits in its implementation.